(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the current competitive business scenario, advertising is being extensively used by every industry to enhance their visibility among the consumers and convert them into life time consumers. This advertisement laid a very powerful impact on children and the result is changing their lifestyle. However, the segment influenced most by these advertisements in a positive or negative manner is the children. The advertising world is getting bigger each day, every minute and every second of the day, people are finding creative writers or designers to showcase their products in a very unique way to the final consumers to make a lasting impression on the people. The purpose of this research study is to examine the impact of television food advertisement on eating behavior of school going children of 10-12 years of age. This research study is to examine the impact of television food advertising on eating behaviour of school going children and the marketing channels used to target Indian children and adolescents. The study has been made by conducting a survey in Kanniyakumari District of Tamil Nadu State. For that, the researcher collected 75 samples from the respondents and percentage, Garret ranking method and t-test used for this study